Assistive Video or Assistive Courseware: What Hearing-impaired Learners Say? - M.Ariffin, A; S.Sobihatun Nur, A; Mazida, A; Massudi, M; Y.Sharifah Nadiya, S (International Journal of Engineering and Technology, 2018)
This paper explains about a comparison between assistive video for hearing-impaired learners (AV4HI) and assistive courseware for hearing-impaired learners (AC4HI).  The rationale is that previous statement was made after learners experience normal courseware, not the courseware specifically designed for them.  Hence, perhaps if the courseware is designed special for them, the hearing-impaired learners would experience differently, and behave more positive upon the AC4HI.  Hence, this paper aims at describing the execution of the comparison.  It involves a 3-stage process: designing the AC4HI, developing the AC4HI, and user experience.  In the end, it was found that users are happy with both, but in terms of content acquisition, they prefer to have notes in the learning material.